Dust Storms Are Associated with an Increase in Outpatient Visits for Rheumatoid Arthritis - Conmin Chen; Chin-Shyan Chen; Tsai-Ching Liu (Atmosphere, 2024)
Our study is the first to illuminate a previously underexplored dimension in the intricate interplay between environmental factors, specifically dust storms (DSs), and rheumatoid arthritis (RA) outcomes. An Auto Regressive Moving Average (ARMA) time-series estimation model was employed to analyze rheumatoid arthritis outpatient visits, dust storms, air pollution, and meteorology data in Taiwan from 2006 to 2012. The results show that females are three times more likely to experience RA-related issues and seek medical attention. Percentage analysis revealed a 10–15% increase in daily RA outpatient visits on post-event days 1 and 2 compared to non-DS days. However, the time-series estimation indicated a delayed and statistically significant (p < 0.05) increase in RA outpatient visits on post-event day 1 for males but not females. Additionally, a significant increase in RA outpatient visits (p < 0.05) was observed on post-event day 1 among individuals aged 61 and above. Environmental factors such as temperature and SO2 showed strong significance across all genders and age groups (p < 0.001). The findings highlight distinct gender and age disparities regarding the impacts of DS on RA outpatient visits, emphasizing the heightened sensitivity of males to environmental pollutants and the vulnerability of the elderly population.